Evaluation of School Administration Management Model Based on Academic Information System - Yunita, Elok Arina; Yulianto, Arief; Sulhadi, Sulhadi (Educational Management, 2021)
The purpose of this study was to evaluate and analyze the academic information system using TAM (Technology Acceptance Model) theory. The most critical infrastructure facility to improve the quality of performance in educational institutions is education technology. Al Quran Terpadu Al Hamidiyah Junior High School has used this system as a model for school administration management. This research approach is quantitative, while data acquisition is made by distributing questionnaires to the required respondents. The data results were collected and then analyzed using descriptive analysis and path analysis with a path model. The results show that Regression Model 1, namely the variables perceived ease of use, usefulness, the behaviour of intention to use, attitude toward using and actual system to use, has the same conclusions. The systems supported by perceived ease of use are easy to learn, available to control, explicit to understand. The indicators of perceived usefulness are sped up work, performance improvement, increased productivity, effectiveness, make work easier and helpful. The variables attitude toward using with indicators are the convenience of using the system, people happy to use, enjoy for users and avoid the monotonous condition. The variables behaviour of intention to use with an indicator are the system has features that help and suit your needs, always try to use and continue in the future. The last is an existing system to use with indicator frequency and duration of use of the system and the actual use of technology in practice.